The Effect of Work Discipline, Work Stress, and Burnout During the Covid-19 Pandemic on the Performance of Employees of the Badan Diklat PKN BPK RI - Muhammad Rio Rahmadhani; Mahendro Sumardjo; Ermawati Ermawati (Universitas Darussalam Gontor, 2022)
This research is a quantitative research that aims to determine whether there is an effect of work discipline, work stress, and burnout during the covid-19 pandemic on the performance of the Badan Diklat PKN BPK RI. In this research, the sample used was 100 people, where data collection was done through Google Form. The data that has been collected is then tested to determine the effect of partial (t-test) and Simultaneous (f-test) using software SPSS Version 25 2020 with a significance level of 5%. The test results show that: (1) Work Discipline has a significant effect on employee performance, (2) Work stress has a significant effect on employee performance, (3) Burnout has a significant effect on employee performance, (4) Work discipline, Job Stress, Burnout affect the performance of employees of Badan Diklat PKN BPK RI.